Use of Medical Reserve Corps Volunteers in a Hospital-based Disaster Exercise. Issue 3 (4th April 2016) - Gist, Ramon; Daniel, Pia; Grock, Andrew; Lin, Chou-jui; Bryant, Clarence; Kohlhoff, Stephan; Roblin, Patricia; Arquilla, Bonnie
Abstract: Introduction: The Medical Reserve Corps (MRC) is a national network of community-based volunteer groups created in 2002 by the Office of the United States Surgeon General (Rockville, Maryland USA) to augment the nation's ability to respond to medical and public health emergencies. However, there is little evidence-based literature available to guide hospitals on the optimal use of medical volunteers and hesitancy on the part of hospitals to use them. Hypothesis/Problem: This study sought to determine how MRC volunteers can be used in hospital-based disasters through their participation in a full-scale exercise. Methods: A full-scale exercise was designed as a "Disaster Olympics, " in which the Emergency Medicine residents were divided into teams tasked with completing one of the following five challenges: victim decontamination, mass casualty/decontamination tent assembly, patient triage and registration during a disaster, point of distribution (POD) site set-up and operation, and infection control management. A surge of patients potentially exposed to avian influenza was the scenario created for the latter three challenges. Some MRC volunteers were assigned clinical roles. These roles included serving as members of the suit support team for victim decontamination, distributing medications at the POD, and managing infection control. Other MRC volunteers functioned as "victim evaluators, " who portrayed the potential avian influenza victims while simultaneously evaluating various aspects of the disaster response. The MRC volunteers provided feedback on their experience and evaluators provided feedback on the performance of the MRC volunteers using evaluation tools. Results: Twenty-eight (90%) MRC volunteers reported that they worked well with the residents and hospital staff, felt the exercise was useful, and were assigned clearly defined roles. However, only 21 (67%) reported that their qualifications were assessed prior to role assignment. For those MRC members who functioned as "victim evaluators, " nine identified errors in aspects of the care they received and the disaster response. Of those who evaluated the MRC, nine (90%) felt that the MRC worked well with the residents and hospital staff. Ten (100%) of these evaluators recommended that MRC volunteers participate in future disaster exercises. Conclusion: Through use of a full-scale exercise, this study was able to identify roles for MRC volunteers in a hospital-based disaster. This study also found MRC volunteers to be uniquely qualified to serve as "victim evaluators" in a hospital-based disaster exercise. R Gist, P Daniel, A Grock, C Lin, C Bryant, S Kohlhoff, P Roblin, B Arquilla .Use of Medical Reserve Corps volunteers in a hospital-based disaster exercise .Prehosp Disaster Med .2016 ;31 (3 ):259 –262 .